Metabolic adjustments in response to ATP spilling by the small DX protein in a Streptomyces strain - Apel, Cécile; Levasseur, Marceau; Lejeune, Clara; Korch, Shaleen B.; Guérard, Florence; David, Michelle; Askora, Ahmed; Litaudon, Marc; Roussi, Fanny; Gakière, Bertrand; Chaput, John; Virolle, Marie-Joelle (Frontiers in Cell and Developmental Biology, 2023)
Abstract ATP wasting is recognized as an efficient strategy to enhance metabolic activity and productivity of specific metabolites in several microorganisms. However, such strategy has been rarely implemented in Streptomyces species whereas antibiotic production by members of this genus is known to be triggered in condition of phosphate limitation that is correlated with a low ATP content. In consequence, to assess the effects of ATP spilling on the primary and specialized metabolisms of Streptomyces, the gene encoding the small synthetic protein DX, that has high affinity for ATP and dephosphorylates ATP into ADP, was cloned in the integrative vector pOSV10 under the control of the strong ErmE promoter. This construct and the empty vector were introduced into the specie Streptomyces albogriseolus / viridodiastaticus yielding A37 and A36, respectively. A37 yielded higher biomass than A36 indicating that the DX-mediated ATP degradation resulted into a stimulation of A37 metabolism, consistently with what was reported in other microorganisms. The comparative analysis of the metabolomes of A36 and A37 revealed that A37 had a lower content in glycolytic and Tricarboxylic Acid Cycle intermediates as well as in amino acids than A36, these metabolites being consumed for biomass generation in A37. In contrast, the abundance of other molecules indicative either of energetic stress (ADP, AMP, UMP, ornithine and thymine), of activation (NAD and threonic acid) or inhibition (citramalic acid, fatty acids, TAG and L-alanine) of the oxidative metabolism, was higher in A37 than in A36. Furthermore, hydroxyl-pyrimidine derivatives and polycyclic aromatic polyketide antibiotics belonging to the angucycline class and thought to have a negative impact on respiration were also more abundantly produced by A37 than by A36. This comparative analysis thus revealed the occurrence in A37 of antagonistic metabolic strategies, namely activation or slowing down of oxidative metabolism and respiration, to maintain the cellular energetic balance. This study thus demonstrated that DX constitutes an efficient biotechnological tool to enhance the expression of the specialized metabolic pathways present in the Streptomyces genomes that may include cryptic pathways. Its use thus might lead to the discovery of novel bioactive molecules potentially useful to human health.